2011
DOI: 10.1111/j.1442-2018.2011.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and religiosity and/or spirituality in college: A longitudinal survey of students in the USA

Abstract: The aim of this study was to conduct a longitudinal test of an explanatory model of depression, where religiosity and/or spirituality (R/S) represents a potentially protective factor in college students in the USA. A Web-based survey was administered monthly to 214 students from religious and public colleges. At 1 month and 6 months, the measures of R/S, depression, stress, and cognitive vulnerability were administered. Between 2 and 5 months, only the measures of stress and depression were administered. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 32 publications
4
27
0
2
Order By: Relevance
“…It terms of social factors, the study also revealed that social support and considering religion as having an impact on one's life were found to be protective of depression. This supports previous studies that identified religiosity and social support as protective factors for depression among college students (Peltzer et al, 2013;Berry and York, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It terms of social factors, the study also revealed that social support and considering religion as having an impact on one's life were found to be protective of depression. This supports previous studies that identified religiosity and social support as protective factors for depression among college students (Peltzer et al, 2013;Berry and York, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Depression occurs more often in students with the following factors: gender female, higher levels of study/ age, lower socioeconomic status, stressful and traumatic situations such as posttraumatic stress and addictive behaviours such as higher alcohol consumption and tobacco use (Ibrahim et al, 2013;Othieno et al, 2014;Peltzer et al, 2013). Other factors associated with depression include poor academic performance, religiosity/ spirituality, and HIV risk behaviour such as substance use in the context of sex (Berry and York, 2011;Othieno et al, 2014;Peltzer et al, 2013;Agardh et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Factors increasing the risk of depression in university students have been identified as follows: 1) sociodemographic factors such as older age or higher study year (Chen et al, 2013;, female gender , lower socioeconomic status (Chen et al, 2013;Ibrahim et al, 2012;Steptoe, Tsuda, Tanaka, & Wardle, 2007); 2) stressful and traumatic life events including life stressors (Afewuya et al, 2006; Reyes-Rodríguez, Rivera-Medina, Cámara-Fuentes, Suárez-Torres, & Bernal, 2013), gender-based violence (Gelaye, Arnold, Williams, Goshu, & Berhane, 2009), witnessing parental violence (Nicodimos, Gelaye, Williams, & Berhane, 2009), and posttraumatic stress disorder (Peltzer, 1998); 3) addictive behaviour including high level of alcohol consumption Peltzer, 2003), smoking (Adewuya, 2006;Adewuya et al, 2006), and gambling (Moode, & Finnigan, 2006); 4) other health risk behaviour such as physical inactivity (Taliaferro, Rienzo, Pigg, Miller, & Dodd, 2009), overweight or obesity (Wilson, Gallivan, Kratzke, & Amatya, 2012;Zhao et al, 2009), HIV risk behaviour (Agardh, Canto-Graae, Ostergren, 2012;Lundberg et al, 2011), sleeping problems (Angelone, Mattei, Sbarbati, & Di Orio, 2011), nonfatal unintentional injury (Chen, Deng, Chn, Kelleher, & Xiang, 2005), and use of skin lightening products (Ladizinski, Mistry, & Kundu, 2011); 5) social variables including social support (Kim, 2001), religiosity and/or spirituality (Berry & York, 2011), low sense of control (Steptoe et al, 2007); and 6) poor academic performance (Yusoff, 2013). among undergraduate students of Obafemi Awolowo University in Nigeria.…”
mentioning
confidence: 98%
“…Namely, the feeling of being understood, valued, and supported by other people helps establish and maintain satisfactory relationships (Canevello & Crocker, 2010). It is thought that the responsive relationship built among group members while responding to and supporting each other's thoughts and feelings was a key contributing factor to overall better interpersonal relationships in the present study.…”
Section: Discussionmentioning
confidence: 76%
“…People with depression have poor interpersonal problem solving skills, which causes more stress in interpersonal relationships. This additional stress then reinforces the feelings of depression, creating a vicious circle (Aanes, Mittelmark, Hetland, 2010;Berry & York, 2011).…”
Section: Introductionmentioning
confidence: 99%